Avaliação de multicaminhamento em diferentes coberturas vegetais - Global Navigation Satellite System (GNSS) x Estação Total. - Pereira, Messias Vargas (Universidade do Vale do Rio dos Sinos, 2017)
The evolution of technology in the field of measurement grows exponentially, in the case of GNSS receivers the same happens, but still present errors in the process of determining a coordinate under the earth's surface. The present work seeks to demonstrate and measure one of the main errors, called multilamination, caused by signal reflection in some objects, such as treetops, buildings, among others. To verify this situation, a six - point survey was carried out on different vegetation cover, eucalyptus plantation, clean area and dense vegetation. Three GNSS surveys were carried out on different days, each with 10, 20 and 30 minute tracking times, and compared to the total station data, since it is not influenced by this error. In the results it can be observed that in areas with forest it is not recommended to use GNSS for precision work, due to the error that varied from 0.178 meters to 0.955 meters. Even so, all data were less than 1.00 meters of linear error, indicating that it could be used in some circumstances.
Keywords: GNSS; Multicaminhamento; Erro Linear; Multicamination; Linear error